A Pd-Catalyzed in situ domino process for mild and quantitative production of 2, 5-dimethylfuran directly from carbohydrates. Issue 9 (20th April 2017) - Li, Hu; Zhao, Wenfeng; Riisager, Anders; Saravanamurugan, Shunmugavel; Wang, Zhongwei; Fang, Zhen; Yang, Song
Abstract : A sustainable catalytic system is developed to be efficient for producing the biofuel 2, 5-dimethylfuran directly from carbohydrate biomass via an in situ domino process under mild conditions. Abstract : An in situ domino process has been developed to be highly efficient for direct and mild conversion of various hexose sugars to the biofuel 2, 5-dimethylfuran in almost quantitative yields, without separation of unstable intermediates at 120 °C in n -butanol, by using polymethylhydrosiloxane and hydrophobic Pd/C as a H-donor and a bifunctional catalyst, respectively. Among the cascade reactions, the hydrosilylation process was confirmed by deuterium-labeling and kinetic studies to be favorable for sugar dehydration and exclusively acts on deoxygenation of in situ formed intermediates including furanic alcohols and aldehydes to DMF via a hydride transfer process that was facilitated by an alcoholic solvent. The catalytic system is more selective than the H2 -participated counterpart, and could be scaled up with only 0.04 mol% catalyst loading, giving DMF in a comparable yield of 85%. Moreover, Pd(0) was demonstrated to be the active species for deoxygenation, and the heterogeneous catalyst exhibited good recyclability with little elemental leaching.